2021
DOI: 10.1007/s13762-021-03686-4
|View full text |Cite
|
Sign up to set email alerts
|

Floating photovoltaic system for Indian artificial reservoirs—an effective approach to reduce evaporation and carbon emission

Abstract: Floating photovoltaic system for reservoirs is a recent innovative technology that is highly advantageous in reducing evaporation while generating solar power. In addition, the integration of floating photovoltaic systems with the existing hydroelectric power plants will increase renewable power production. The present study aims to assess the electrical performance of floating photovoltaic systems in major reservoirs with existing hydroelectric power plants in India. The reservoirs with large water surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Research has indicated that the implementation of aquatic photovoltaic systems yields a substantial carbon reduction effect, resulting in the reduction of emissions by an impressive 3.3 million tons annually [18]. It can reduce the eutrophication of water bodies and reduce the concentration of chlorophyll and nitrate in water bodies [17,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that the implementation of aquatic photovoltaic systems yields a substantial carbon reduction effect, resulting in the reduction of emissions by an impressive 3.3 million tons annually [18]. It can reduce the eutrophication of water bodies and reduce the concentration of chlorophyll and nitrate in water bodies [17,40].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of evaporation is influenced by temperature and inversely proportional to humidity levels, and through the adjustment of the angle of the photovoltaic (PV) tilt, it has been observed that a significant reduction in evaporation can be achieved. The implementation of single-axis tracking mechanisms or novel photosensitizers has the potential to induce varied levels of energy generation over the course of a year [17][18][19]. Despite the effectiveness of FPV, no relevant experiments have been conducted for waterborne photovoltaic (WPV), which holds practical and economic value in fishery-photovoltaic complementary fish ponds.…”
Section: Introductionmentioning
confidence: 99%
“…It links the size of society's population P, economic affluence A, the level of production technology T, and environmental stress I. The impact of these three socioeconomic behaviors and environmental stress is quantified using a mathematical function (Ravichandran and Panneerselvam, 2022;Sadiq et al, 2022). The IPAT model function is shown in Eq.…”
Section: Decomposition Of Factors Influencing Carbon Emissions Of Ene...mentioning
confidence: 99%
“…Such hybrid systems provide better energy security with increased generation capacity and better hydropower generation due to reduction of evaporation loss (Gonzalez et al 2021 ). Ravichandran and Panneerselvam ( 2021 ) evaluated an FSPV system of 5 MW capacities on an artificial reservoir in India. The FSPV provides annual electricity of 160 GWh and saves 1.4 million cubic meters of water by reducing evaporation losses.…”
Section: Introductionmentioning
confidence: 99%